2011
DOI: 10.1007/s10750-011-0728-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a constructed wetland for retention of sediment-associated phosphorus

Abstract: A constructed wetland (2.1 ha; 2% of catchment area) in southeast Sweden, in a catchment with 35% arable land on clay soils, was investigated with respect to phosphorus (P) retention, focusing on particulate P (PP) and sediment accretion. The aims were to i) estimate P retention and identify the dominating retention processes; ii) investigate how well estimates of P retention based on inflow-outflow measurements compared with the amount of P accumulated in the sediment.In-and outflow of P was measured during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
5
18
0
Order By: Relevance
“…This possible error in the retention estimate would be relatively more important in low loaded wetlands, and in sections with dense stands of emergent plants (c.f. Johannesson et al, 2011). A difference in sediment composition that supports this discussion was indeed observed in two of the wetlands in the current study (Fig.…”
Section: Retention and Modeled Loadsupporting
confidence: 88%
“…This possible error in the retention estimate would be relatively more important in low loaded wetlands, and in sections with dense stands of emergent plants (c.f. Johannesson et al, 2011). A difference in sediment composition that supports this discussion was indeed observed in two of the wetlands in the current study (Fig.…”
Section: Retention and Modeled Loadsupporting
confidence: 88%
“…A possible reason for this could be that the long period with ice cover caused anoxia that reduced iron in the wetland sediment, which released the P bound to iron. Similar observations were made in another Swedish FWS wetland, where it was suggested that accumulated litter and organic sediment caused the development of anoxic conditions, with the subsequent release of iron‐bound P during ice cover periods (Johannesson et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Johannesson et al (2011) showed that the PP concentration in the outflow from a constructed wetland was stable even though the PP concentration in the inflow fluctuated drastically. This indicates a background production of PP in the wetlands.…”
Section: Introductionmentioning
confidence: 99%